2019
DOI: 10.1021/acs.iecr.9b00557
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pr on Ni–Mg–Al Mixed Oxides Synthesized by Microwave-Assisted Self-Combustion for Dry Reforming of Methane

Abstract: Pr (1–12% wt) promoted Ni–Mg–Al mixed oxides were synthesized by the microwave-assisted self-combustion method. The promoting role of Pr on the physical and chemical properties and the catalytic performance in dry reforming of methane (DRM) were studied. Several techniques were used to evaluate the chemical composition and the thermal, structural, reductive, basic, textural, and morphological properties of the oxides. Catalytic stability tests in DRM at 600 °C after reduction in reactant flow at 700 °C were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 64 publications
(134 reference statements)
0
16
0
Order By: Relevance
“…Syngas derived from the renewable biomass process has attracted tremendous interests for the generation of various value-added chemicals and fuel, yet biogas inevitably contains carbon dioxide (CO 2 ) and methane (CH 4 ) during the biomass gasification. , Therefore, there is a growing concern on converting the two greenhouse gases to syngas as a desirable procedure for the upgrading of biomass-derived syngas. Dry reforming of methane (DRM) has been regarded as an alternative route for the effective utilization of CO 2 and CH 4 to the syngas. Generally, DRM reaction requires high reaction temperature (>650 °C) because of its endothermic characteristic. Besides noble-based catalysts, Ni-based catalysts exhibit comparable activity and selectivity to H 2 ; whereas the sintering of Ni nanoparticles (NPs) (low Tammann temperature of Ni) and coke deposition (CO and CH 4 dissociation) quickly deactivate the catalyst during the high-temperature reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Syngas derived from the renewable biomass process has attracted tremendous interests for the generation of various value-added chemicals and fuel, yet biogas inevitably contains carbon dioxide (CO 2 ) and methane (CH 4 ) during the biomass gasification. , Therefore, there is a growing concern on converting the two greenhouse gases to syngas as a desirable procedure for the upgrading of biomass-derived syngas. Dry reforming of methane (DRM) has been regarded as an alternative route for the effective utilization of CO 2 and CH 4 to the syngas. Generally, DRM reaction requires high reaction temperature (>650 °C) because of its endothermic characteristic. Besides noble-based catalysts, Ni-based catalysts exhibit comparable activity and selectivity to H 2 ; whereas the sintering of Ni nanoparticles (NPs) (low Tammann temperature of Ni) and coke deposition (CO and CH 4 dissociation) quickly deactivate the catalyst during the high-temperature reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, other side reactions such as gasification of carbon deposits and the Boudouard reaction could have also taken place [13,40]. Moreover, in the study of Ojeda-Niño et al [41] a series of Ni-Mg-Al hydrotalcites were synthesized by the microwave-assisted self-combustion method and promoted by different concentrations of praseodymium, i.e., 1.2 wt.%, 5.9 wt.% and 11.4 wt.%.…”
Section: Reducibility Basicity Ni Dispersion and Crystallite Sizementioning
confidence: 99%
“…In the study of microwave-assisted DRM activity with respect to the stability, Ojeda-Niño et al (2019) found that the incorporation of Pr not only significantly enhance the thermal stability for the Ni-Mg-Al catalysts at hightemperature microwave-assisted DRM but also promote the CO 2 adsorption in a capture-release reversible dynamic depending on the basicity strength. Overall, they discovered that the Pr loading did not has a direct correlation Fig.…”
Section: Metal-based Catalystsmentioning
confidence: 99%